Стійкість еритроцитів щурів різного віку до гіпертонічних умов середовища. - Коба, Л.В.; Шапкіна, О.О.; Жуйкова, А.Є.; Бондаренко, В.А. (Вісник проблем біології і медицини. – 2018. – Вип.3 (145).- C.389-392., 2018)
Еритроцити 1- і 12-місячних щурів піддавали гіпертонічному шоку (4,0 М NaCl) після початкової інкубації в розчинах сахарози (0,27 – 1,0 М) на протязі 2, 10, 30, 60 хв. В гіпертонічних неелектролітних середовищах частина клітин тварин обох вікових груп зазнає гемолізу. Рівень їх пошкодження залежить від тонічності розчину, часу експонування, віку тварин. Початкова інкубація еритроцитів 1- і 12-місячних щурів в розчинах сахарози підвищує їх чутливість до подальшого переносу в 4,0 М NaCl. --------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- Age-related changes in the animal organism develop at the level of cells, organs, and physiological systems. Changes in the membrane structures of cells at different stages of ontogeny can have a latent character, manifest themselves in certain experimental conditions beyond the physiological norm. Stability of mammalian erythrocytes to hypertonic influence is determined by the cytoskeleton-plasma membrane complex. Its condition can be changed by exposing erythrocytes under certain conditions at the stage of pre-incubation before the action of the main stress factor. The aim of the study was to investigate the osmotic resistance of erythrocytes of 1- and 12-month-old white rats to hypertonic shock (4.0 M NaCl) after preliminary incubation in sucrose solutions (0.27-1.0 M). Object and methods of research. The experiments were performed on red blood cells of male Wistar rats of 1 and 12 months. The washed red blood cells were preincubated in sucrose solutions for 2, 10, 30, 60 minutes at 37°C and then transferred to 4.0 M NaCl at the same temperature. The cells were precipitated by centrifugation. The hemoglobin content in the supernantant was measured spectrophotometrically. The level of hemolysis in the sample was expressed as a percentage of the sample with 100% hemolysis. Statistical processing of the results was carried out by conventional methods using Mann-Whitney criteria. Result and discussion. It was found that the rat erythrocytes are hemolysed in sucrose solutions during the preincubation stage. During the first 2 minutes under these conditions not more than 10% of the cells of animals of both age groups are damaged. Longer incubation of erythrocytes in non-electrolyte media is responsible for a decrease in their osmotic stability. Rat erythrocytes of the younger age group are less stable compared to the cells of 12-month-old animals under the same conditions of tonicity and incubation time. So the level of hemolysis of cells of 1-month-old animals in hypertonic sucrose solutions reaches 44% by the 30th minute and 60% by the 60th minute, and 12-month animals, respectively, 28% and 42% under the same incubation conditions. The character of the effect of pre-incubation conditions on the osmotic resistance of erythrocytes to further transfer to 4.0 M NaCl depends on the conditions at this stage and the age of the animals. A decrease in the level of hemolysis in 4.0 M NaCl is observed only after a 2-minute incubation of cells of 1-month-old rats in solution with 0.5 M sucrose. With an increase in the pre-exposure time (30 and 60 min), the erythrocytes of both age groups become sensitive to a transfer in 4.0 M NaCl. In this case, hemolytic damage in hypertonic saline solution of erythrocytes increases after preliminary incubation in media with 0.5-1.0 M sucrose. Thus, erythrocytes of 1-month-old rats undergo hemolysis in sucrose solutions during the pre-incubation stage with an increase in its duration to 30-60 min. The erythrocytes of 12-month-old rats have a large osmotic resistance to hypertonic conditions in non-electrolyte media, but are substantially sensitized to further transfer to 4.0 M NaCl with increasing time of their initial exposure in them. Conclusions. It is shown that the resistance of rat erythrocytes to hypertonic solutions of sucrose depends on the tonicity of the medium, the incubation time and the age of the animals. Incubation in hypertonic sucrose solutions, mainly, sensitizes the erythrocytes of rats to hypertonic shock (4.0 M NaCl).
STABILITY OF DIFFERENT AGE RAT ERYTHROCYTES TO HYPERTONIC MEDIUM
Коба ЛВ, Шапкіна ОО, Жуйкова АЄ, Бондаренко ВА. Стійкість еритроцитів щурів різного віку до гіпертонічних умов середовища. Вісник проблем біології і медицини. 2018; 3(145): 389-92.
Keywords: еритроцити щурів; гіпертонічний шок; віковий статус; сахарозне середовище